(untitled) (Harmoni, 2018)
A discourse about Pesantren in Protestant bastion from the New Order Era to Reform Era is significant to study for building a strong, stable, wealthy and democratic life. Pondok Karya Pembangunan Manado is Pesantren to be the focus of research. Bacause the region and the composition of interethnic and interfaith inhabitants were highly representative. This study used the qualitative-explorative type with sociological approach. The result showed that (1) There were three relation typologies including structural relation, organizational relation and cultural relations (2) There were five factors that strengthened┬á the peace which consisted of construction of┬á local religion, interfaith leadership system, construction of inter-offspring, curriculum centralization and santri mobilization. Thus, in summary the relations and peace activity always appeared┬á in public spaces to develop intracommunal and intercommunal engagement. ┬á